1998
DOI: 10.1002/(sici)1096-9861(19980126)390:4<515::aid-cne5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and branching patterns of round, type 2 corticopulvinar axons

Abstract: Corticopulvinar connections consist of at least two morphologically distinct subpopulations. In one subgroup (E, type 1), axons have an "elongated" terminal field and thin, spinous terminations; in the other (R, type 2), axons have a small, round arbor and large, beaded terminations. Previous work (Rockland, 1996) indicates that E-type axons from several occipitotemporal areas branch extensively within and sometimes between pulvinar subdivisions, but that R-type axons tend to have spatially delimited arbors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 52 publications
5
53
0
Order By: Relevance
“…Most of its inputs originate from the cerebral cortex and the superior colliculus (SC). The LGN receives a massive cortical projection from V1 cortical layer 6, and the PULV receives afferents from layers 5 and 6 of several cortical areas (Rockland, 1998;Wang et al, 2002;Shipp, 2003 Fitzpatrick at al. (1985); Callaway and Wiser (1996) Layer 2/3 cells V1 → Layer 2/3 cells V1 D Recurrent connections (grouping) in 2/3.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of its inputs originate from the cerebral cortex and the superior colliculus (SC). The LGN receives a massive cortical projection from V1 cortical layer 6, and the PULV receives afferents from layers 5 and 6 of several cortical areas (Rockland, 1998;Wang et al, 2002;Shipp, 2003 Fitzpatrick at al. (1985); Callaway and Wiser (1996) Layer 2/3 cells V1 → Layer 2/3 cells V1 D Recurrent connections (grouping) in 2/3.…”
Section: 21mentioning
confidence: 99%
“…The longer and smaller the dendrite, the more attenuated the post-synaptic current will be at the soma. Differential dendritic termination and synaptic weight magnitudes can be used to simulate the proposed functional differentiation between driving, large, round (R-type) thalamic vesicles occurring at retinothalamic and thalamocortical synapses, and elongated, small vesicles that characterize many corticothalamic terminations (Rockland, 1998;Sherman and Guillery, 2001). Elongated and round-type synapses also widely occur at the level of corticocortial synapses (Rockland, 2002).…”
Section: Neurotransmitter Releasementioning
confidence: 99%
“…We have associated RL terminals in higher order thalamic nuclei as emanating from layer 5 of the cortex. Evidence that this occurs is available from many examples (reviewed in Sherman, 2005;Sherman and Guillery, 2006): from visual cortex to the pulvinar Rockland, 1998;Rouiller and Welker, 2000), from somatosensory cortex to the posterior nucleus (Hoogland et al, 1991;; and from the auditory cortex to the magnocellular part of the medial geniculate nucleus (Ojima, 1994;Bartlett et al, 2000). Evidence for this also exists for the medial dorsal nucleus (Schwartz et al, 1991).…”
Section: Drivers Versus Modulatorsmentioning
confidence: 99%
“…Tracer injections confined to areas 17 and 18 label type II corticothalamic terminals in the LP nucleus that originate from layer V cells and type I corticothalamic terminals in the dorsal lateral geniculate nucleus (dLGN) that originate from layer VI cells (Ojima et al, 1996). In the LP nucleus, area 17 corticothalamic terminals are RL profiles that participate in glomeruli (Vidnyánszky et al, 1996;Feig and Harting, 1998), whereas, in the dLGN, area 17 corticothalamic terminals are RS profiles that contact small caliber dendrites outside of glomeruli (Jones and Powell, 1969;Vidnyánszky and Hamori, 1994;Vidnyánszky et al, 1996;Erisir et al, 1997).The recognition that corticothalamic terminals originating from layers V or VI of the striate cortex may serve different functions within the thalamus has led to a renewed interest in the cortical inputs to the LP-pulvinar complex (Rockland, 1994(Rockland, , 1996(Rockland, , 1998Bourassa and Deschênes, 1995;Vidnyánszky et al, 1996; Anderson et al, 1998;Feig and Harting, 1998;Li et al, 2003). Because the synaptic connections of large type II corticothalamic terminals in the LP-pulvinar nucleus are similar to the synaptic connections of retinal terminals in the dLGN, it has been suggested that the type II corticothalamic terminals may provide the primary or driving input to the LP-pulvinar complex (Guillery, 1995; Rodrigo-Angulo and ReinosoSuarez, 1995;Sherman and Guillery, 1996;Feig and Harting, 1998).…”
mentioning
confidence: 99%